Growth and Yield of Cowpea (Vigna unguiculata L.) Under Different Levels of Phosphorous and Seed Inoculation with Rhizobium - Poudel, Ankita; Adhikari, Bishnu Bilas; Shrestha, Jiban (Agronomy Journal of Nepal, 2023)
Cowpea (Vigna unguiculata L.) is a major source of protein and an important component of Nepal’s cropping systems. However, yields are very low due to a lack of improved cultivars, poor management practices, and limited input use. The objective of this study was to evaluate the effects of rhizobia inoculant and P on cowpea growth and yield. A field study was carried out in Bharatpur-11, Chitwan, Nepal, during the spring season of 2022, using a randomized complete block design with three replications and eight treatments. The treatments included four different phosphorus doses (20, 40, 60, and 80 kg ha-1) and seed inoculation (un-inoculated and inoculated). The rhizobium-inoculated plants produced significantly higher grain yield (1.27 t ha-1) and various yield-attributing parameters than un-inoculated plants. Phosphorus fertilizer at 40 kg ha-1 produced a higher grain yield (1.41 t ha-1) than other phosphorus doses. The combination of rhizobium inoculation and application of phosphorus at the rate 40 kg ha-1 yielded the highest grain yield (1.53 t ha-1). The results show that phosphorus dose of 40 kg ha-1 combined with Rhizobium inoculation with seed has the potential to improve cowpea grain yield.